Studi Kritis terhadap Ilmu Balaghah Klasik - Husein Aziz (Islamica: Jurnal Studi Keislaman, 2007)
Classical Balaghah has been developed theoretically since the era of B. Mu?tazand culminated in the development in the era of al-Qahir al-Jurjani. But since then, ifhas ceased to improve. In the modern era, this science has only been applied, annotated,redefined and classified. As a consequence, Balaghah turned out to be both dry andstatic, incapable of further improvement and adaptation to new circumstances. It is inthis context that this science should be revisited so that new formulation may be fund.